FEMALE START-UP ENTREPRENEURS IN THE KINGDOM OF SAUDI ARABIA: CHALLENGES AND OPPORTUNITIES - Zahya Abdulaziz Al-Maghrabi, Florabel Nieva (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aimed to determine the challenges and opportunities of female start-up entrepreneur who are in the Kingdom of Saudi Arabia. The study had used both quantitative and qualitative data gathering tools such as articles and journals. Meanwhile, qualitative data collection tools included interviewing thirteen female entrepreneurs that have established their start-ups. The study had discussed twelve Saudi female entrepreneurs who had set up their businesses in jewelry, clothing, pet care, and developing games. The business operation were ranges from three months to two years with minimum of two employees and a maximum of seventeen employees working. Most respondents had relied on funding their business by families and self-funded their business. In addition, some respondents mentioned that funded their business with bank loans. The business women had faced legal challenges such as denial of giving loans to start-up, legal challenges such as long duration of issuing permits and licensing and social problems such as risk of being harassed or mislead by investors or potential partner as well as technological/material issues confronted